Extending the fossil record of Miocene neotropical epiphyte communities - Kathrin Feldberg; Ulla Kaasalainen; Yuriy S. Mamontov; S. Robbert Gradstein; Alfons Schäfer-Verwimp; Pradeep K. Divakar; Alexander R. Schmidt (Fossil Record)
Dominican amber (15–20 Ma) and Mexican amber (15–23 Ma) are valuable sources of fossil epiphytic bryophytes, ferns, and lichens. Both ambers derive from resins of Hymenaea, a genus in the Fabaceae family still occurring in Mexico, Central America, and the Caribbean today. The amber inclusions provide rare glimpses into Miocene neotropical epiphyte communities in life-like preservation. In this study, we extend the fossil record of these communities and describe Frullania chiapasensis and Thysananthus patrickmuelleri, two new fossil species of leafy liverworts from Mexican amber. Frullania chiapasensis is the fourth representative of this genus from tropical amber. The genus Thysananthus is rather diverse in Dominican amber, and it is here newly recorded from Mexican amber. Additionally, we treat five new fossils at genus level, including one leafy liverwort (Lejeunea sp.) as well as three lichens from Dominican amber and one lichen from Mexican amber, all belonging to the extant genus Parmotrema. All four cryptogamic genera are common extant elements of tropical and subtropical forests. The new fossil evidence substantiates that Miocene neotropical cryptogamic communities were very similar to extant ones at generic level.